Formation of 3-MCPD and glycidyl esters in biscuits produced using soybean oil-based diacylglycerol stearin-shortening blends: impacts of different baking temperatures and blending ratios - Abdul Kadir, Nur Shafika; Khor, Yih Phing; Lee, Yi Jane; Lan, Dongming; Qi, Suijian; Wang, Yonghua; Tan, Chin Ping (Elsevier, 2022)
Diacylglycerol (DAG) is commonly known as one of the precursors for 3-monochloropropane-1,2-diol esters (3-MCPDE) and glycidyl esters (GE) formation. Besides, 3-MCPDE and GE are heat-induced contaminants which can be formed in fat-containing baked products during the baking process. This study attempted to replace the conventional palm-based shortening (SH) with a healthier fat, namely soybean oil-based diacylglycerol stearin (SDAG) in producing biscuits. The effects of different baking temperatures (200, 210 and 220 °C) and SDAG:SH fat blend ratios (0:100, 60:40 (D64S), 80:20 (D82S), 100:0, w/w) towards the biscuits’ physical properties were evaluated. Moreover, the oxidative stability, 3-MCPDPE and GE formation in the fats extracted from the biscuits were also investigated. SDAG-produced biscuit showed slight reductions in the spread ratio compared to the SH-produced biscuit. The elevated baking temperatures resulted in biscuits with increased hardness and low moisture content. Pure SDAG and the other fat blends exhibited significant (p < 0.05) poorer oxidative stability than SH. However, D64S was found to be more oxidative stable compared to SDAG and D82S. The D64S fat blend exhibited the lowest 3-MCPDE and GE formation rates among all fat samples with the increasing baking temperatures. Furthermore, the amount of 3-MCPDE and GE detected in the fats extracted from the biscuits baked at highest temperature (220 °C) were still within the safety limit. In overall, better quality biscuits were produced when lower baking temperature (200 °C) was used as all biscuits baked with different fats showed similar textural properties (hardness and cohesiveness), higher oxidative stability and lower formation of 3-MCPDE and GE compared to biscuits baked at higher temperatures. The findings justified the potential of D64S fat blend in replacing the conventional SH in producing healthier biscuits.